Pengaruh The Influence of Organizational Culture in Creating Quality Organizational Development - Ningsih, Sri Rahayu (Indikator Pendidikan Indonesia, 2022)
Organizational culture is an important and very strategic element in the development and progress of organizations in the business world, government, educational institutions, and socio-religious organizations. Organizational culture does not just exist but must be created. maintained, and strengthened, even changed to suit the internal and external demands of the organization. Organizational culture will affect organizational effectiveness. So far, many studies have concluded that a strong organizational culture will make members more satisfied, and motivated and have a greater commitment to the organization. Besides that, a strong organizational culture will be able to increase the commitment, enthusiasm, and loyalty of members to the organization. In this research method, we use the descriptive method. The result show that organizational culture will affect individuals and organizational processes so that culture will create pressure on people in the organization to think and act in ways that are consistent with the existing culture. The organizational culture of educational institutions is strongly influenced by leadership behavior. Good leadership behavior will be able to create a conducive organizational culture.